2021
DOI: 10.21608/jppp.2021.155790
|View full text |Cite
|
Sign up to set email alerts
|

Diadegma aegyptiator Shaumer 1966 (Hymenoptera: Ichneumonidae): New Record Parasitoid on the Rib Miner, Scrobipalpa ocellatella Boyd. (Lepidoptera: Gelechiidae) in Egyptian Sugar Beet Fields

Abstract: The larvae of the rib miner,Scrobipalpa ocellatella Boyd feed on the sugar beet leaves and roots causing huge damage in such a way that the root rot and thus it caused a reduction in the yield of roots and the sugar content in the roots. Parasitoids are the most effective natural enemies for insect biological control. In nature, several parasitoids were observed to be potential bio-agents of serious crop pests. The future of "insecticide-less" pest management will be driven by a bouquet of parasitoids and pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In another study, Bazazo and Ibrahim (2019) calculated the mean of parasitism of D. oranginator on S. Ocellatella was 55.17, 60.46 and 68.91% for the three cultivations, respectively. In addition, Bazazo and Hassan (2021) monitored the overall parasitism to D. aegyptiator on S. Ocellatella larvae with 24.52 and 31.03% during the two seasons, respectively. these findings demonstrated that these parasitoids complex of S. ocellatella are able to manage this dangerous insect pest.…”
Section: Seasonal Abundance Of Parasitism Percentages On S Ocellatell...mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Bazazo and Ibrahim (2019) calculated the mean of parasitism of D. oranginator on S. Ocellatella was 55.17, 60.46 and 68.91% for the three cultivations, respectively. In addition, Bazazo and Hassan (2021) monitored the overall parasitism to D. aegyptiator on S. Ocellatella larvae with 24.52 and 31.03% during the two seasons, respectively. these findings demonstrated that these parasitoids complex of S. ocellatella are able to manage this dangerous insect pest.…”
Section: Seasonal Abundance Of Parasitism Percentages On S Ocellatell...mentioning
confidence: 99%
“…In addition, Bazazo and Ibrahim (2019) estimated the parasitism rates by Diadegma oranginator Aub to be 55.17, 60.46 and 68.91% for three cultivations, respectively. Further, mean parasitism by Diadegma aegyptiator Shaumer on S. ocellatella larvae ranged from 24.52 to 31.03% in the first and second seasons, respectively (Bazazo and Hassan, 2021).…”
mentioning
confidence: 95%